Volunteering in a mental health service in Uganda: challenges and rewards. (November 2019) - Martin, Fiona
Abstract : Fiona Martin is a psychiatry trainee who spent 6 months volunteering in a mental health service in Uganda between her core and higher psychiatry training. In this article, she reflects upon this experience, including the challenges and rewards, and in particular the benefits to training of such an experience.